Calcium Carbonate Precipitation by Bacillus and Sporosarcina Strains Isolated from Concrete and Analysis of the Bacterial Community of Concrete - Kim, Hyun Jung; Eom, Hyo Jung; Park, Chulwoo; Jung, Jaejoon; Shin, Bora; Kim, Wook; Chung, Namhyun; Choi, In-Geol; Park, Woojun (Journal of microbiology and biotechnology, 2016)
Microbially induced calcium carbonate precipitation (CCP) is a long-standing but re-emerging environmental engineering process for production of self-healing concrete, bioremediation, and long-term storage of CO2. CCP-capable bacteria, two Bacillus strains (JH3 and JH7) and one Sporosarcina strain (HYO08), were isolated from two samples of concrete and characterized phylogenetically. Calcium carbonate crystals precipitated by the three strains were morphologically distinct according to field emission scanning electron microscopy. Energy dispersive X-ray spectrometry mapping confirmed biomineralization via extracellular calcium carbonate production. The three strains differed in their physiological characteristics: growth at alkali pH and high NaCl concentrations, and urease activity. Sporosarcina sp. HYO08 and Bacillus sp. JH7 were more alkali- and halotolerant, respectively. Analysis of the community from the same concrete samples using barcoded pyrosequencing revealed that the relative abundance of Bacillus and Sporosarcina species was low, which indicated low culturability of other dominant bacteria. This study suggests that calcium carbonate crystals with different properties can be produced by various CCP-capable strains, and other novel isolates await discovery.